2019
DOI: 10.1007/978-3-030-20965-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche Dynamics and Correlations in Neural Systems

Abstract: The existence of power law distributions is only a first requirement in the validation of the critical behavior of a system. Long-range spatio-temporal correlations are fundamental for the spontaneous neuronal activity to be the expression of a system acting close to a critical point. This chapter focuses on temporal correlations and avalanche dynamics in the spontaneous activity of cortex slice cultures and in the resting fMRI BOLD signal. Long-range correlations are investigated by means of the scaling of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Power-law regimes (A) and (B) are followed by a faster decay of the probability P (Δ t ) for Δ t ’s longer than 1 s, which may be related to delta oscillations. The non-exponential, power-law quiet time distribution implies that neural cascades of activity are strongly correlated [63, 12, 35, 31, 33, 30]. Indeed, the distribution P (Δ t ) calculated after random phase shuffling (Materials and Methods) of the original brain signals is exponential (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Power-law regimes (A) and (B) are followed by a faster decay of the probability P (Δ t ) for Δ t ’s longer than 1 s, which may be related to delta oscillations. The non-exponential, power-law quiet time distribution implies that neural cascades of activity are strongly correlated [63, 12, 35, 31, 33, 30]. Indeed, the distribution P (Δ t ) calculated after random phase shuffling (Materials and Methods) of the original brain signals is exponential (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The double power-law, non-exponential quiet time distribution, as well as the autocorrelation C ( t ), implies that neural cascades of activity are strongly correlated [50, 51, 37, 52, 53, 54], and indicates that the nature of correlations in the cascading process depends on the time scales. Indeed, the distribution P (Δ t ) calculated after random phase shuffling (STAR Methods) of the original brain signals is exponential (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for single power law distributed inter-event times, the rate of change in one state variable requires the introduction of a fractional order derivative (Shlesinger, 1987; West, 2010; Svenkeson et al, 2016). Of note, as demonstrated in Lombardi et al (2019), the distribution of inter-event times (among successive events) can not only shed light on the nature of the operator governing the rate of change (dynamics), but also allow us to study the hierarchical temporal organization of the neuronal avalanches (i.e., an ensemble of neurons that fire close-in-time) and the existence of a critical behavior. Nevertheless, the set of critical exponents characterizing the neuronal spontaneous activity in control conditions and in the presence of folic acid are different (Yaghoubi et al, 2018) suggesting the existence of different universality classes.…”
Section: Biological (Genomic Proteomic Physiological) Complexity: Mmentioning
confidence: 99%
“…Rigorous mathematical analysis shows that many such genomic, proteomic and physiological processes possess time dependent, long-range dependence, and multi-fractal characteristics (Goldberger and West, 1987; Ivanov et al, 2001; Wink et al, 2008; Bassingthwaighte et al, 2013; Ghorbani and Bogdan, 2013; Bohara et al, 2017; Akhrif et al, 2018; Ghorbani et al, 2018; Racz et al, 2018b). For instance, Lombardi et al (2019) demonstrated that the existence of long-range temporal correlations (dependence) is an accurate marker of “healthy brains.” Moreover, mathematical investigations of physiological processes collected from the individuals suffering from various diseases revealed specific patterns, for example, a decrease in correlation in both temporal and fractal behavior (Ivanov et al, 1999; Stanley et al, 1999; Kotani et al, 2005; Gierałtowski et al, 2012). For instance, the ratio between the short-term and long-term scaling exponents was demonstrated in Platiša et al (2019) to discriminate between patients experiencing heart failure, providing crucial information where the levels of the cardiac autonomic nervous system control, age, or the left ventricular ejection fraction could not.…”
Section: Introductionmentioning
confidence: 99%